Development of Student Worksheets with PhET Based on PjBL Model in Physics Learning to Improve High School Students' Scientific Creativity - Sumo*, Maimon; Soeharto, Soeharto; Kamariyah, El Indahnia; Umamah, Chairatul; Angraini, Mila Rosa (Universitas Syiah Kuala, 2025)
Scientific creativity is an important thing that every individual must have to answer the challenges of the 21st century. However, in reality, the results of physics research show that the science abilities of Indonesian students are still relatively low, especially in the fields of creativity and innovation. This study aims to produce project-based student worksheet (LKPD) integrated with valid and reliable PhET. This study uses the research and development (RD) method with a 4D development model, which consists of four stages, namely definition, design, development, and dissemination. The instruments in the study used to collect data were validation sheets and student response questionnaire sheets. The results showed that the LKPD integration of PhET obtained an average validity score of 3.95 and a reliability level of 96.25%, including in the very valid and reliable category. The results of the student response questionnaire showed that 93% responded in the very positive category. The conclusion is that this LKPD integration of PhET is proven to be valid and reliable so that it can be an effective learning material for learning physics on global warming and climate change. This study contributes to the development of innovative and relevant learning media to improve the quality of students' physics learning. The limitations of this study have limitations on the application of the 4D model, which only covers the development and Validation stages. Therefore, the implementation of LKPD in the field is needed to improve the scientific creativity of high school students